Melhora do equilíbrio postural em mulheres idosas com o uso de informação sensorial adicional - Leme, Gianluca Loyolla Montanari (2017)
ABSTRACT The natural process of human aging has morphological and physiological changes, such as balance and gait, increasing the risk of falling. Some studies have investigated the use of additional sensory information to improve body balance using a soft touch on a rigid and stationary surface, which showed a significant reduction in the body oscillation. Effects of the additional sensory information were evaluated during gait on elderly women. We evaluated 30 elderly women aged 60 or older. Sensory information was added by an infrapatellar bandage. Participants performed the tests proposed by the Dynamic Gait Index (DGI), the Timed Up and Go (TUG), and the 10-Meter Walk Test (10MWT), with and without infrapatellar bandage. Data comparisons were carried out by using paired t test and Wilcoxon test with p ≤ 0.05. There was a significant difference in the TUG (without bandage: 10.13 ± 2.1, with bandage: 9.71 ± 2.1, p = 0.0007) and DGI test (without bandage: 20.65 ± 2 1; with bandage: 22.1 ± 2.1, p = 0.002). There was no significant difference in the use of 10MWT sensory addition. The results showed that the use of additional sensory information generated by the infrapatellar bandage promoted improvement of functional mobility and physical performance in elderly women.